Establishment of thromboelastography reference intervals by indirect method and relevant factor analyses. Issue 6 (31st January 2020) - Cheng, Daye; Li, Xiaoying; Zhao, Shuo; Hao, Yiwen
Abstract: Thromboelastography (TEG) as a global coagulation test has been continuously developed for many decades in either research or clinical practice. The versatility of TEG test leads to difficulty in standardization and result interpretation. Reference intervals (RIs) of TEG may be one of the most controversial factors that influence its wide applications. RIs establishment with the traditional method is time‐consuming and laborious as well as beyond general laboratory capability. Indirect method using stored data and with statistical calculation and small cost is emerging as an alternative approach for RIs determination. Gender, age, or both affect RIs and must be taken into account before RIs estimation. The present study retrospectively collected a total of 930 TEG results as subjects and established RIs with indirect method for Kaolin‐activated TEG, including the parameters of R, K, αAngle, MA, and CI. Furthermore, gender, age, and gender‐dependent age subsets analyses were performed to determine their effects on RIs of TEG. In this study, we found that TEG parameters showed more hypercoagulability in female than male, most of the measured TEG variables were significantly associated with aging, but only in male statistical significance was found among different age stratification and 60‐year‐old could be considered as cutting point to differentiate coagulation ability in male. In addition, RIs of TEG were estimated by indirect method suitably and verified to be valid in our study. Finally, the RIs of TEG by indirect method were basically significantly different to the RIs recommended by manufacturer, but the consistent percentage is relatively high in the most of measured parameters. In conclusion, it is suggestive that the indirect method for RIs establishment is feasible, but relevant factors, such as gender and age, specifically gender‐dependent age effect, should be considered before RIs determinations.